2017
DOI: 10.1134/s0006297917080090
|View full text |Cite
|
Sign up to set email alerts
|

SkQ1 regulates expression of Nrf2, ARE-controlled genes encoding antioxidant enzymes, and their activity in cerebral cortex under oxidative stress

Abstract: The administration of SkQ1 to rats at the dose of 50 nmol/kg for five days significantly increased the mRNA levels of transcription factor Nrf2 and of Nrf2-controlled genes encoding antioxidant enzymes SOD1, SOD2, CAT, and GPx4, whereas changes in the level of mRNA of SOD3 in the cerebral cortex of the rat brain were not significant. This was accompanied by activation of antioxidant enzymes (SOD, CAT, GPx, and GST) and increase in reduced glutathione concentration. Under oxidative stress induced by hyperoxia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…A huge body of evidence revealed that the antioxidant SOD is activated by the Nrf2 pathway against different conditions of oxidative stress (Milani, Ambrosi, Gammoh, Blandini, & Cereda, 2013; Vnukov et al, 2017). Nrf2 is a vital transcription factor commonly expressed in organs with high oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A huge body of evidence revealed that the antioxidant SOD is activated by the Nrf2 pathway against different conditions of oxidative stress (Milani, Ambrosi, Gammoh, Blandini, & Cereda, 2013; Vnukov et al, 2017). Nrf2 is a vital transcription factor commonly expressed in organs with high oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1, NQO1, and SOD are the antioxidant genes regulated by Nrf2 binding to antioxidant response elements. 28,29 These genes play important roles in response to oxidative stress and have cytoprotective effects. 30 HO-1 can catalyze the degradation of heme, and the degradation products also have antioxidant functions.…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 pathway has been identified to be the pivotal regulator for oxidative stress, which participates in transcription of many enzymes, such as SOD and GPX (Vnukov et al 2017). To explore the exact mechanism of Sch B neuroprotective effect in the anxiety disorder, the western blot method was used to verify the conjecture that whether Sch B altered expression of molecular targets commonly associated with oxidative stress.…”
Section: Effect Of Sch B On the Nrf2/keap1 Expression In Stress-inducmentioning
confidence: 99%